Phased multi‐target areal development competitions: Algorithms for competitor allocation - Lahdenperä, Pertti (International Journal of Strategic Property Management, 2009)
The prevailing practice in new areal real estate development is for public and private actors to perform their duties by turns. Yet, the planning process could benefit from simultaneous contributions from society and developers and their designers. That, again, requires that the municipality selects the private partner consortia prior to completion of the local detailed plan through a competition in order to find the most potential actors and the best ideas for implementation of an urban structure of high quality. Candidates will be attracted by offering them the right to implement a residential/business block as a developer. The several blocks involved in an areal development project, and the laboriousness of producing competitive solutions, require a well planned selection process. A novel multi‐target competition process was developed which is presented in this paper with special emphasis on the allocation algorithms that allow selecting the most qualified competitors for parallel follow‐up competitions from among a large group of registered candidates. The approach was tested in an actual real estate development project in the municipal district of Vuores which was the original reason for launching the study. First Publish Online: 18 Oct 2010